Leveraging Digital Technologies for Enhanced Part-Time Lecturer Payment Tracking in Higher Education - Charles Ochieng’ Oguk; Roy Obiero Awiti (IJRDO -Journal of Computer Science Engineering, 2025)
This study addresses the critical issue of inefficient payment management for part-time lecturers in higher education institutions, leading to significant financial distress and potential negative impacts on educational quality. Drawing on the findings from a mixed-methods study involving descriptive and experimental research designs, the paper focuses specifically on the modeling and testing of a digital tracking system for part-time lecturer payments. Current manual and fragmented systems used in universities often lack transparency, remote tracking capabilities, and efficient processing mechanisms, resulting in delayed or non-payments and administrative challenges like double payments and lost documents. User and functional requirements for a digital tracking system were established, highlighting the need for a user-friendly, accessible (web-based/mobile), secure, and integrated platform with features such as payment tracking, automated processing, payment approval, notifications, and comprehensive reporting. Based on these requirements, a digital system model utilizing modern web technologies (Bootstrap, PHP, HTML5, CSS3, JavaScript) and an MVC framework was developed and subsequently tested. The model incorporates a centralized database, a web application interface, a QR code generator for unique claim identification, and a workflow tracking mechanism to monitor claims from submission to payment. Testing revealed the system’s potential to improve efficiency, transparency, and accuracy in managing payments, providing lecturers with the ability to track their claims remotely and enhancing institutional financial management and reputation. The findings demonstrate the feasibility and necessity of adopting digital solutions to address longstanding payment issues, contributing to financial stability for part-time academic staff and supporting the quality of education.